'A slight lesion in the grey matter': The gothic brain in Arthur Machen's The Great God Pan. Issue 1 (1st April 2016) - Rebry, Natasha
In Arthur's Machen's The Great God Pan (1894), a neurological experiment produces a demonic woman who brings about the mental, physical and social deterioration of almost all with whom she comes into contact. In this text, as in much of his other fiction, Machen characterizes the brain as an interstitial site between mind and body as well as a portal to supernatural forces, demonstrating an engagement with philosophical issues raised by nineteenth-century mental physiology and neurology. Through its portrayal of neurological theories and experimental practices, The Great God Pan demonstrates anxiety over the biological reductionism and materialism of late Victorian mental science, especially the threat to self-governance and the potential erosion of social stability occasioned by a lack of will or spiritual force guiding human thought and action.